A rare presentation of aorto-bronchial fistula and the relevance of open repair in endovascular era - Zulkifli, M. Faizal Effendi; Marican, M. Azri; Radzif, Abdul Rashid M.; Azmi, Muhammad Ibrahim; Muhammad, Mohamad Arif; Jasid, Abdul Muiz; Kamarulzaman, M. Hamzah (International Surgery Journal, 2020)
Aorto-bronchial fistula is a rare but potentially fatal condition due to torrential bleeding from erosion of aneurysmal wall into bronchial wall or lung parenchyma. It is usually associated with infection, lung transplantation, pulmonary malignancies, atherosclerotic and mycotic aneurysms, and anastomotic pseudoaneurysms after open or endovascular surgery. The typical presentation usually manifested by haemoptysis, but rarely the patient also can be presented with hematemesis and this will delay the definitive treatment. Surgical or endovascular repair is mandatory because non-operative management will lead to a poor prognosis due to massive bleeding from the fistula. We would like to present a unique case of an elderly man presented with intermittent haematemesis, in which he later developed profound haemoptysis and diagnosed with ABF. Although in the era of endovascular, the ABF was successfully treated via open thoracotomy, resection of thoracic aorta aneurysm, left lower lobe lobectomy, and completed with aortic repair using Gelweave aortic graft.